Belt and Road Forum 2019 : BRI 2.0 In The Making? - Rana, Pradumna Bickram (2019)
At the second Belt and Road Forum in Beijing last week, China acknowledged the criticisms labelled against the BRI and pledged to reform it a number of ways. If these pledges are implemented, and cooperation with development partners and stake-holding countries increases, we could see “BRI 2.0” emerging which could lead to a win-win situation for all.